Optical coherence tomography for in-situ weld seam monitoring in absorber-free laser transmission welding - Maiwald, Frederik; Fries, Fabian; Schulze, Julian; Honnerová, Petra; Hierl, Stefan; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2025)
Optical and medical devices are frequently made of polymers and place high demands on precision, cleanliness, and reliability of the manufacturing processes used. Absorber-free laser transmission welding is well-suited for joining these devices: the energy input is contactless, no adhesives, additives, or absorbers are required, and the fiber lasers used enable precise weld seams. As the weld seam geometry is decisive for the joint strength and thus crucial for the quality of the product, the welding process is monitored in-situ using optical coherence tomography (OCT). Subsequently, the weld seam geometry is identified automatically using the AI model "Segment Anything" (SAM), which performs semantic segmentation of the OCT data without requiring any training from the user. Welding tests using polyamide 6 indicate that the seam size is measured with an accuracy of a few hundredths of a millimeter, showing excellent agreement with microscopic images of microtome sections.
CRIS-Team Scopus Importer:2025-04-25
Keywords: image processing; in-situ process monitoring; laser welding; optical coherence tomography; polymers; SAM